Electrochemical ionic actuator and method for manufacturing thereof
Patent Information
- Application Number
- CN202310713040.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-06-16
- Publication Date
- 2026-10-13
- Estimated Expiration
- 2043-06-16
AI Technical Summary
但MXene片层间具有自堆叠效应和其本身较低的机械性能会影响电极材料的性能
[0023]本发明通过在碳纳米管(CNTs)上生长Fe3O4磁性粒子,使CNTs具备一定磁性,可以通过磁场诱导CNTs进行有序排列,使其在MXene片层间形成导电网络和离子通道,抑制MXene片层间的自堆叠效应的同时,提高了MXene/CNTs@Fe3O4电极材料的电荷存贮能力和电化学性能。
Smart Images

Figure CN116963579B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of ion actuator technology, and in particular to an electrochemical ion actuator and its preparation method. Background Technology
[0002] Currently, soft robot research mainly focuses on dielectric elastomer actuators, pneumatic actuators, electrochemical ion actuators, soft magnetic actuators, and stimulus-responsive polymers. Flexible electrochemical actuators (ion actuators) have advantages such as light weight, large bending curvature, rapid response, low-voltage operation, and ease of manufacturing, making them a key research area in soft robotics. Electrochemical actuators consist of a central electrolyte layer and symmetrically covered electrode layers on both sides. The reversible migration of anions and cations in the electrode layers determines the actuator's bending strain capability; therefore, the electrode materials need to meet requirements such as high capacitance, high conductivity, and high ion mobility. MXene, as a novel two-dimensional material, possesses advantages such as naturally high conductivity, strong hydrophilicity, abundant surface functional groups, and adjustable interlayer spacing, and is widely used in batteries, supercapacitors, sensors, and energy fields. In recent years, MXene has also become a mainstream electrode material for electrochemical ion actuators.
[0003] Patent CN111740000A discloses an MXene composite material-based electrochemical actuator, its preparation method, and its applications, demonstrating the great potential of MXene as an electrode layer for electrochemical actuators. However, the self-stacking effect between MXene layers and its relatively low mechanical properties can affect the performance of the electrode material. Summary of the Invention
[0004] To address the shortcomings of existing technologies, this invention provides an electrochemical ion-type actuator and its preparation method, which improves the performance of the actuator electrode layer by combining MXene with other materials.
[0005] The technical solution adopted in this invention is as follows:
[0006] This application provides a method for preparing an MXene / CNTs@Fe3O4 electrochemical actuator, including:
[0007] Carbon nanotubes loaded with Fe3O4 magnetic particles on their surface were prepared by chemical coprecipitation to obtain a CNTs@Fe3O4 solution. The MXene suspension and the CNTs@Fe3O4 solution were mixed and ultrasonically treated. Under magnetic field induction, the CNTs@Fe3O4 were uniformly and orderly arranged between the MXene sheets to prepare an MXene / CNTs@Fe3O4 mixed solution.
[0008] Perfluorosulfonic acid resin and ionic liquid are dissolved in dimethylformamide at a certain temperature and stirred evenly to prepare a solution; the solution is poured into a mold and dried to form an electrolyte film;
[0009] The MXene / CNTs@Fe3O4 mixed solution was uniformly drop-coated onto one side of the electrolyte film using a drop-coating method. After drying at a certain temperature, the film was flipped over and the MXene / CNTs@Fe3O4 mixed solution was drop-coated onto the other side of the electrolyte film. The film was then dried again to obtain the MXene / CNTs@Fe3O4 electrochemical actuator.
[0010] The further technical solution is as follows:
[0011] The preparation of carbon nanotubes with Fe3O4 magnetic particles on the surface using the chemical co-precipitation method yields a CNTs@Fe3O4 solution, comprising:
[0012] Carboxylated multi-walled carbon nanotubes were dispersed in deionized water, and FeCl3·6H2O and FeCl2·4H2O were added. The mixture was stirred evenly and then ultrasonically dispersed in an ultrasonic cleaner.
[0013] After removal, dilute ammonia solution is added dropwise until the solution becomes alkaline. The mixture is stirred under a certain temperature condition. After the reaction is complete, the carbon nanotubes with Fe3O4 magnetic particles loaded on the surface are extracted with a magnet, i.e., CNTs@Fe3O4 magnetic particles.
[0014] CNTs@Fe3O4 magnetic particles were repeatedly washed with deionized water until neutral, then dried and ground into powder.
[0015] Finally, it was dissolved in deionized water and ultrasonically dispersed to obtain a CNTs@Fe3O4 solution.
[0016] The dispersant used for ultrasonic dispersion is sodium dodecyl sulfate.
[0017] After mixing the MXene suspension and the CNTs@Fe3O4 solution, the mixture was ultrasonically treated in an ultrasonic cleaner for a certain period of time to uniformly disperse the CNTs@Fe3O4 between the MXene sheets.
[0018] The concentration of the MXene suspension is 2–8 mg / ml, and the concentration of the CNTs@Fe3O4 solution is 0.2–1 mg / ml.
[0019] The MXene suspension was obtained by treating Ti3AlC2 with LiF and HCl.
[0020] The ionic liquid is EMIBF4.
[0021] This application also provides an MXene / CNTs@Fe3O4 electrochemical actuator prepared by the above preparation method, comprising two electrode layers and an electrolyte layer sandwiched between them. The electrode layers are made of an MXene / CNTs@Fe3O4 composite material composed of two-dimensional material MXene and multi-walled carbon nanotubes (CNTs) with magnetic Fe3O4 particles grown on them. The electrolyte layer is made of a composite material composed of perfluorosulfonic acid resin and ionic liquid EMIBF4.
[0022] The beneficial effects of this invention are as follows:
[0023] This invention grows Fe3O4 magnetic particles on carbon nanotubes (CNTs), giving the CNTs a certain degree of magnetism. The magnetic field can induce the CNTs to align in an orderly manner, forming a conductive network and ion channels between MXene sheets. This suppresses the self-stacking effect between MXene sheets while improving the charge storage capacity and electrochemical performance of the MXene / CNTs@Fe3O4 electrode material.
[0024] Due to the excellent mechanical properties of CNTs, the flexibility and ductility of MXene / CNTs@Fe3O4 electrode materials are also improved.
[0025] Other features and advantages of the invention will be set forth in the description which follows, and will be apparent in part from the description, or may be learned by practicing the invention. Attached Figure Description
[0026] Figure 1 This is a SEM image of the cross-section of the electrode layer of the MXene / CNTs@Fe3O4 electrochemical actuator prepared in Example 1 of the present invention.
[0027] Figure 2 Cyclic voltammetry curves of the electrode layer material of the MXene / CNTs@Fe3O4 electrochemical actuator prepared in Example 1 of this invention in the paramagnetic field direction and perpendicular magnetic field direction.
[0028] Figure 3 Electrochemical impedance spectroscopy (EIS) spectra of the electrode layer material of the MXene / CNTs@Fe3O4 electrochemical actuator prepared in Example 1 of this invention in the paramagnetic field direction and the perpendicular magnetic field direction.
[0029] Figure 4 Charge-discharge curves of the electrode layer material of the MXene / CNTs@Fe3O4 electrochemical actuator prepared in Example 1 of this invention in the paramagnetic field direction and the perpendicular magnetic field direction.
[0030] Figure 5The graph shows the specific capacitance values of the electrode layer material of the MXene / CNTs@Fe3O4 electrochemical actuator prepared in Example 1 of this invention under different mass ratios and different magnetic field strengths.
[0031] Figure 6 This is a schematic diagram of the structure of the MXene / CNTs@Fe3O4 electrochemical actuator prepared in Example 1 of the present invention.
[0032] In the diagram: 1. Electrode layer; 2. Electrolyte layer. Detailed Implementation
[0033] The specific embodiments of the present invention are described below with reference to the accompanying drawings.
[0034] This application provides a method for preparing an MXene / CNTs@Fe3O4 electrochemical actuator, including:
[0035] Carbon nanotubes (CNTs) with Fe3O4 magnetic particles loaded on their surface were prepared by chemical coprecipitation to obtain a CNTs@Fe3O4 solution. The MXene suspension and the CNTs@Fe3O4 solution were mixed and ultrasonically treated to induce the CNTs@Fe3O4 to be uniformly and orderly arranged between the MXene sheets under magnetic field induction, thus preparing an MXene / CNTs@Fe3O4 mixed solution.
[0036] The perfluorosulfonic acid resin (Nafio) and ionic liquid are dissolved in dimethylformamide (DMF) at a certain temperature and stirred evenly to prepare a solution; the solution is poured into a mold and dried to form an electrolyte film;
[0037] The MXene / CNTs@Fe3O4 mixed solution was uniformly drop-coated onto one side of the electrolyte film using a drop-coating method. After drying at a certain temperature, the film was flipped over and the MXene / CNTs@Fe3O4 mixed solution was drop-coated onto the other side of the electrolyte film. The film was then dried again to obtain the MXene / CNTs@Fe3O4 electrochemical actuator.
[0038] Among them, carbon nanotubes with Fe3O4 magnetic particles loaded on their surface were prepared by chemical co-precipitation to obtain CNTs@Fe3O4 solution, including:
[0039] Carboxylated multi-walled carbon nanotubes were dispersed in deionized water, and FeCl3·6H2O and FeCl2·4H2O were added. The mixture was stirred evenly and then ultrasonically dispersed in an ultrasonic cleaner.
[0040] After removal, dilute ammonia solution is added dropwise until the solution becomes alkaline. The mixture is stirred under a certain temperature condition. After the reaction is complete, the carbon nanotubes with Fe3O4 magnetic particles loaded on the surface are extracted with a magnet, i.e., CNTs@Fe3O4 magnetic particles.
[0041] CNTs@Fe3O4 magnetic particles were repeatedly washed with deionized water until neutral, then dried and ground into powder.
[0042] Finally, it was dissolved in deionized water and ultrasonically dispersed to obtain a CNTs@Fe3O4 solution.
[0043] The concentration of the MXene suspension is 2–8 mg / ml, and the concentration of the CNTs@Fe3O4 solution is 0.2–1 mg / ml.
[0044] The MXene suspension was prepared by treating Ti3AlC2 with LiF / HCl.
[0045] The ionic liquid is EMIBF4.
[0046] This application also provides an MXene / CNTs@Fe3O4 electrochemical actuator prepared by the method described above.
[0047] This application utilizes a magnetic field to induce the growth of Fe3O4 CNTs (i.e., CNTs@Fe3O4 magnetic particles) to form an ordered arrangement between MXene sheets, creating a well-conducting network. MXene exhibits a multi-layered, stacked structure, and CNTs@Fe3O4 can be uniformly and orderly arranged between these layers. This suppresses the self-stacking effect between MXene sheets while improving the electrode's charge storage capacity and migration speed, thus contributing to enhanced electrochemical performance of the electrode material. Simultaneously, CNTs also possess good mechanical properties, further improving the mechanical properties of the electrode material.
[0048] The following specific embodiments further illustrate the preparation method of the MXene / CNTs@Fe3O4 electrochemical actuator of this application. Example 1
[0049] (1) First, dissolve 4g LiF in 50ml 9M HCl, then gradually add 3g Ti3AlC2 powder to the above solution and stir with a magnetic stirrer for 24 hours;
[0050] After the reaction was complete, the resulting acidic solution was washed repeatedly with deionized water until neutral. Finally, the resulting neutral solution was subjected to ultrasonic treatment and centrifugation, and the volume was adjusted to 180 ml. The ultrasonic power was 200 W, the ultrasonic time was 4 h, the centrifugation speed was 3500 rpm, and the number of centrifugations was 1, to obtain a 3.5 mg / ml MXene suspension.
[0051] (2) Disperse 0.4g of carboxylated multi-walled carbon nanotubes in 400ml of deionized water, then add 3.2g of FeCl3·6H2O and 1.6g of FeCl2·4H2O, stir for 1 hour, then place in a 200W ultrasonic cleaner and sonicate for 30 minutes. After taking it out, add dilute ammonia solution dropwise until pH=12, stir at 65℃ for 2 hours. After the reaction is complete, use a magnet to extract the CNTs@Fe3O4 magnetic particles; wash them repeatedly with deionized water until neutral, then dry and grind them into powder.
[0052] Dissolve 4g of sodium dodecyl sulfate (SDS) in 200ml of deionized water, then add 40mg of CNTs@Fe3O4, and sonicate in a 200W cell disruptor for two hours to obtain a 0.2mg / ml CNTs@Fe3O4 solution.
[0053] (3) Take 17.15 ml of MXene suspension and 3.03 ml of CNTs@Fe3O4 solution and mix them. Sonicate in a 200W ultrasonic cleaner for 1 hour, and ensure that the water level in the ultrasonic cleaner is not lower than the liquid level of the mixed solution (to ensure that CNTs@Fe3O4 is evenly dispersed between MXene sheets). Under the induction of a magnetic field, CNTs@Fe3O4 are arranged in an orderly manner to obtain MXene / CNTs@Fe3O4 solution.
[0054] (4) Dissolve 1g of perfluorosulfonic acid resin Nafion and 1.5g of EMIBF4 in 20mL of dimethylformamide (DMF) at 60℃. Stir the solution at 60℃ for 24 hours using a magnetic stirrer to form a homogeneous solution. Then pour the solution into a Teflon mold and dry it at 60℃ for 8 hours. Finally, an electrolyte film with a size of 40mm×40mm is formed on the mold.
[0055] (5) Take 10 ml of the prepared MXene / CNTs@Fe3O4 solution and drop it onto the electrolyte membrane. Dry it at 60°C for 6 hours and remove it. Turn it over and drop it onto the membrane again. Continue to drop 10 ml of MXene / CNTs@Fe3O4 solution and dry it at 60°C for 6 hours to obtain the MXene / CNTs@Fe3O4 electrochemical actuator.
[0056] See Figure 6 In Example 1, an MXene / CNTs@Fe3O4 electrochemical actuator structure was prepared, which is a sandwich structure with two electrode layers 1 and an electrolyte layer 2 sandwiched in the middle. The electrode layer 1 is an MXene / CNTs@Fe3O4 composite material composed of two-dimensional material MXene and multi-walled carbon nanotubes (CNTs) with magnetic Fe3O4 particles grown on it. The electrolyte layer 2 is a composite material composed of perfluorosulfonic acid resin and ionic liquid EMIBF4.
[0057] To further verify the performance of the electrochemical actuator obtained in Example 1, performance tests were conducted, and the results are as follows:
[0058] like Figure 1 The image shows a cross-sectional SEM image of the electrode layer of the MXene / CNTs@Fe3O4 electrochemical actuator. In the figure, 1(a) and (b) are images of different positions of the electrode layer cross-section, and the magnetic field direction is shown in the figure.
[0059] Figure 1 (a) shows a cross-sectional view of the electrode layer closer to the magnetic field. As can be seen from the figure, a large number of CNTs@Fe3O4 are accumulated in the MXene layer due to the influence of the magnetic field, and the orientation of CNTs@Fe3O4 is consistent with the direction of the magnetic field. Figure 1 Image (b) shows a cross-sectional view of the electrode layer farther from the magnetic field. Compared to image (a), a small amount of CNTs@Fe3O4 aggregates in the MXene interlayer under the influence of the magnetic field in image (b), and the orientation of the CNTs@Fe3O4 is consistent with the direction of the magnetic field. This indicates that CNTs@Fe3O4 moves between the MXene layers under the influence of the magnetic field, and its direction is affected by the direction of the magnetic field. Furthermore, uniformly distributed granular Fe3O4 particles can be seen on the surface of the CNTs in both images (a) and (b), indicating the successful growth of Fe3O4 magnetic particles on the CNTs.
[0060] like Figure 2 The figure shows the cyclic voltammetry curves of the electrode layer material in the MXene / CNTs@Fe3O4 electrochemical actuator in the paramagnetic field direction and the perpendicular magnetic field direction.
[0061] Figure 2 The horizontal axis represents voltage, the vertical axis represents current, and 20mV / s represents the scanning speed. Figure 2 The curve represents the current response obtained by controlling the voltage. The specific capacitance (the amount of charge that can be charged or discharged per unit mass of electrode material) can be calculated from the enclosed area of the curve to indicate the quality of the electrode material. The figure shows that the MXene / CNTs@Fe3O4 material has the highest specific capacitance along the magnetic field direction, indicating that the ordered arrangement of CNTs@Fe3O4 within the MXene sheets facilitates ion insertion into the MXene sheets, thereby improving electrochemical performance.
[0062] like Figure 3 The figure shows the electrochemical impedance spectroscopy of the electrode layer material in the MXene / CNTs@Fe3O4 electrochemical actuator in the direction parallel to the magnetic field and perpendicular to the magnetic field.
[0063] Figure 3The horizontal axis represents the real part of the impedance, and the vertical axis represents the imaginary part of the impedance, representing the impedance plane as a whole. As shown in the figure, in the low-frequency region, the slope of the MXene / CNTs@Fe3O4 material along the magnetic field direction is greater than that of the other two materials, indicating that the capacitance performance of MXene / CNTs@Fe3O4 material along the magnetic field direction is superior to the other two materials. In the high-frequency region, the semicircle diameter of MXene / CNTs@Fe3O4 material along the magnetic field direction is smaller than that perpendicular to the magnetic field direction, indicating that the former has a lower charge transfer resistance. This further suggests that the ordered arrangement of CNTs@Fe3O4 among the MXene sheets facilitates ion insertion into the MXene sheets.
[0064] like Figure 4 As shown, the charge-discharge curves of the electrode layer material in the MXene / CNTs@Fe3O4 electrochemical actuator are shown in the paramagnetic field direction and the perpendicular magnetic field direction.
[0065] Figure 4 The horizontal axis represents time, the vertical axis represents voltage, and 500mA / g represents current density. Figure 4 This represents the voltage change over time at a certain current density. The figure shows that the MXene / CNTs@Fe3O4 material exhibits an isosceles triangular shape along the magnetic field direction, conforming to an ideal capacitor with a small voltage drop. At a current density of 500 mA / g, the discharge time of the MXene / CNTs@Fe3O4 material along the magnetic field direction is longer than that perpendicular to the magnetic field direction, indicating that the ordered arrangement of CNTs@Fe3O4 between the MXene sheets can form a good conductive network to improve electrochemical performance.
[0066] like Figure 5 The figure shows the specific capacitance values of the electrode layer material in the MXene / CNTs@Fe3O4 electrochemical actuator under different mass ratios and different magnetic field strengths.
[0067] Figure 5 The horizontal axis represents the content percentage, the vertical axis represents the magnetic field strength, the vertical axis represents the specific capacitance, 20 mV / s represents the scan rate, and 1 M H₂SO₄ represents the electrolyte solution. As shown in the figure, the MXene / CNTs@Fe₃O₄ material exhibits the highest specific capacitance and best electrochemical performance at a content percentage of 5 wt% and a magnetic field strength of 10248 G. Furthermore, with increasing content percentage, the electrochemical performance of the MXene / CNTs@Fe₃O₄ material initially increases and then decreases compared to MXene, indicating that excessive addition of CNTs@Fe₃O₄ negatively impacts electrochemical performance.
[0068] It will be understood by those skilled in the art that the above description is merely a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention has been described in detail with reference to the foregoing embodiments, those skilled in the art can still modify the technical solutions described in the foregoing embodiments or make equivalent substitutions for some of the technical features. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the protection scope of the present invention.
Claims
1. A method for preparing an MXene / CNTs@Fe3O4 electrochemical actuator, characterized in that, include: Carbon nanotubes loaded with Fe3O4 magnetic particles on their surface were prepared by chemical coprecipitation to obtain a CNTs@Fe3O4 solution. The MXene suspension and the CNTs@Fe3O4 solution were mixed and ultrasonically treated. Under magnetic field induction, the CNTs@Fe3O4 were uniformly and orderly arranged between the MXene sheets to prepare an MXene / CNTs@Fe3O4 mixed solution. Perfluorosulfonic acid resin and ionic liquid are dissolved in dimethylformamide at a certain temperature and stirred evenly to prepare a solution; the solution is poured into a mold and dried to form an electrolyte film; The MXene / CNTs@Fe3O4 mixed solution was uniformly drop-coated onto one side of the electrolyte film using a drop-coating method. After drying at a certain temperature, the film was flipped over and the MXene / CNTs@Fe3O4 mixed solution was drop-coated onto the other side of the electrolyte film. The film was then dried again to obtain the MXene / CNTs@Fe3O4 electrochemical actuator.
2. The method for preparing the MXene / CNTs@Fe3O4 electrochemical actuator according to claim 1, characterized in that, The preparation of carbon nanotubes with Fe3O4 magnetic particles on the surface using the chemical co-precipitation method yields a CNTs@Fe3O4 solution, comprising: Carboxylated multi-walled carbon nanotubes were dispersed in deionized water, and FeCl3·6H2O and FeCl2·4H2O were added. The mixture was stirred evenly and then ultrasonically dispersed in an ultrasonic cleaner. After removal, dilute ammonia solution is added dropwise until the solution becomes alkaline. The mixture is stirred under a certain temperature condition. After the reaction is complete, the carbon nanotubes with Fe3O4 magnetic particles loaded on the surface are extracted with a magnet, i.e., CNTs@Fe3O4 magnetic particles. CNTs@Fe3O4 magnetic particles were repeatedly washed with deionized water until neutral, then dried and ground into powder. Finally, it was dissolved in deionized water and ultrasonically dispersed to obtain a CNTs@Fe3O4 solution.
3. The method for preparing the MXene / CNTs@Fe3O4 electrochemical actuator according to claim 2, characterized in that, The dispersant used for ultrasonic dispersion is sodium dodecyl sulfate.
4. The method for preparing the MXene / CNTs@Fe3O4 electrochemical actuator according to claim 1, characterized in that, After mixing the MXene suspension and the CNTs@Fe3O4 solution, the mixture was ultrasonically treated in an ultrasonic cleaner for a certain period of time to uniformly disperse the CNTs@Fe3O4 between the MXene sheets.
5. The method for preparing the MXene / CNTs@Fe3O4 electrochemical actuator according to claim 4, characterized in that, The concentration of the MXene suspension is 2–8 mg / ml, and the concentration of the CNTs@Fe3O4 solution is 0.2–1 mg / ml.
6. The method for preparing the MXene / CNTs@Fe3O4 electrochemical actuator according to claim 1, characterized in that, The MXene suspension was obtained by treating Ti3AlC2 with LiF and HCl.
7. The method for preparing the MXene / CNTs@Fe3O4 electrochemical actuator according to claim 1, characterized in that, The ionic liquid is EMIBF4.
8. An MXene / CNTs@Fe3O4 electrochemical actuator prepared by the method according to any one of claims 1 to 7, characterized in that, It includes two electrode layers and an electrolyte layer sandwiched between them. The electrode layers are made of MXene / CNTs@Fe3O4 composite material, which is composed of two-dimensional material MXene and multi-walled carbon nanotubes (CNTs) with magnetic particles Fe3O4 grown on them. The electrolyte layer is made of a composite material composed of perfluorosulfonic acid resin and ionic liquid EMIBF4.
Citation Information
Patent Citations
Nucleation and growth of tin particles into three dimensional composite active anode for lithium high capacity energy storage device
CN102714299A
MXene composite material based electrochemical actuator and preparation method and application thereof
CN111740000A